5x - 7y = 5 (subtract both sides by 5x) -7y = -5x + 5 (divide both sides by -7) y = (5x - 5)/7 If you want to solve for y = 0, then x = 1.
Add 4x - 2 to each side: 5x = 5 x = 1
0
4x - 8 = 5x 1) Add 8 to both sides. 4x - 8 (+ 8) = 5x (+ 8) Becomes 4x = 5x + 8 2) Subtrate 5x from both sides. 4x (- 5x) = 8 Becomes -1x = 8 Reduced to -x = 8 3) Multiply both sides by -1. Becomes x = -8
(1) 5x+y=-12 (2) 7x-3y=-30 From (1) one gets y = -12-5x Put into (2) 7x-3y = 7x -3 (-12-5x) = 7x + 36 +15 x = 22x +36=-30 22x = -30-36 = -66 so x = -3 and y=-12-5x = -12-5x-3= 3 The solution is (-3,3)
-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11
5x+1=20 5x=20-1 5x=19 5x/5=19/5 x=19/5
If: 5x+1 = 21 Then: 5x = 21-1 => 5x = 20 Divide both sides by 5 and so x = 4
y = 2x -1 y = 5x -13 So: 5x -13 = 2x -1 5x -2x = 13 -1 3x = 12 x = 4 and by substituting y = 7
x=8
5x + 9 = 4Subtract 9 from each side:5x = -5Divide each side by 5:x = -1
7x -3 = 5x + 1 solve for xadd three to both sides7x = 5x + 4subtract 5x from both sides2x = 4divide both sides by 2x = 2
y = 5x + 1 is nota direct variation.y = 5x + 1 is nota direct variation.y = 5x + 1 is nota direct variation.y = 5x + 1 is nota direct variation.
7X-1=9+5X. add 1 to both sides 7X=10+5X. Subtract 5X and get 2X=10 divide by 2 and x=5
2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x
To solve for two unknowns (x and y) it is necessary to have two independent equations.
the question is to solve (x^2-5x+5)^(x^2-36)=1